1981
DOI: 10.1038/291629a0
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal inducibility of rat α2u globulin genes in transfected mouse cells

Abstract: Two different genes coding for the hormonally regulated rat liver protein alpha 2u globulin were introduced into mouse Ltk- cells through co-transfection with the HSV-1 thymidine kinase gene. Three to ten copies of the alpha 2u globulin genes were detected several tk+ clones, over 50% of which could be induced with dexamethasone, the produce alha 2u globulin mRNA and protein. This suggests that the information necessary for hormonal response is contained in the DNA fragment used for transfer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
1

Year Published

1981
1981
1998
1998

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(45 citation statements)
references
References 17 publications
3
41
0
1
Order By: Relevance
“…Two rat a2u-globulin genes introduced by co-transfection with the herpes virus-thymidine kinase gene in the tk-L cells were transcribed and expressed as secreted a2u-globulin. Both the mRNA and the protein levels rose in response to the steroid (Kurtz, 1981). Similar results in the same system were obtained with the rat (Moore et al, 1982) and human somatotropin genes and showed that DNA sequences required for induction reside within 500bp of 5'-flanking DNA (Robins et al, 1982).…”
Section: Glucocorticoids Modulate Mrna Concentrationsupporting
confidence: 69%
“…Two rat a2u-globulin genes introduced by co-transfection with the herpes virus-thymidine kinase gene in the tk-L cells were transcribed and expressed as secreted a2u-globulin. Both the mRNA and the protein levels rose in response to the steroid (Kurtz, 1981). Similar results in the same system were obtained with the rat (Moore et al, 1982) and human somatotropin genes and showed that DNA sequences required for induction reside within 500bp of 5'-flanking DNA (Robins et al, 1982).…”
Section: Glucocorticoids Modulate Mrna Concentrationsupporting
confidence: 69%
“…Using these techniques, investigators have introduced several eucaryotic genes into foreign cells, and their expression has been demonstrated at the nucleic acid level, protein level, or both (Mulligan et al, 1979;Wigler et al, 1979;DeRobertis and Olson, 1979;Capecchi, 1980;Grosschedl and Birnstiel, 1980;Lai et al, 1980). Furthermore, there are recent reports of regulation of gene expression in these systems (Kurtz, 1981;Buetti and Diggelmann, 1981;Hynes et al, 1981). For other genes, we anticipate that expression or regulation may be difficult to demonstrate because the appropriate cell type may not be amenable to analysis in culture, or developmental programming may be essential.…”
Section: Introductionmentioning
confidence: 99%
“…In FaC1 a portion of the RNA was lost, which accounts for the decreased signal. (29)(30)(31)(32), and a few of these appear to be transcriptionally activated given the proper induction signal (33,34), cell background plays an important role in the regulation of tissue-specific gene expression (33,(35)(36)(37) As shown in other systems (38,39), the orientation of the insert is probably not a major factor in the regulation of expression for the chicken actin genes, because the genes are being transcribed from their respective promotors, as judged by primer extensions, and are flanked on their 5' and 3' sides by a similar length of sequence. The level of expression may, however, depend on orientation, and this is under study.…”
Section: Introduction Of the Chicken Actin Genes Into Myogenic C2mentioning
confidence: 99%